Podcasts de divulgação científica: um estudo interdisciplinar a partir da experiência de coprodução com a Rádio UFSCar - Murta, Cíntia Maria Gomes (Universidade Federal de São Carlos, 2025)
This applied and exploratory study aims to examine the challenges involved in the production of scientific podcasts within the university setting, with an emphasis on co-productions developed in partnership with UFSCar Radio. Based on the Science, Technology, and Society (STS) framework, the research employs an interdisciplinary approach to investigate the historical, social, and cultural factors that have shaped the representation of science in Brazil, addressing the obstacles to fostering a participatory scientific culture in contemporary contexts. The study further explores the interplay between communicative practices and emerging media technologies, with a focus on orality and sound media in digital and mediatized environments. A multiple case study approach was used to map and systematize the scientific podcasts produced by the UFSCar community between 2023 and 2024, under UFSCar’s Radio Public Call initiative: A Matemática no Divã; De Frame a Frame; Gero Papo; Prosa Geodiversa; Saúde e Trabalho; Voz Indígena. The investigation identifies key production challenges, strategies implemented, and outcomes achieved, considering the producers’ professional backgrounds and the objectives of their audio projects. The methodology included documentay analysis and in-depth interviews. Results highlight factors influencing the observed experiences, such as institutional support and the producers’ enthusiasm for sound-based communication. Limitations, including time constraints, resource scarcity, and barriers to audience interaction, are also noted as critical issues requiring resolution to enhance the effectiveness of scientific dissemination. The findings underscore the need for more dialogical, integrated, and interdisciplinary communication strategies, emphasizing the podcast’s potential as a strategic medium for science popularization.
SCIENTIFIC PODCASTS: An Interdisciplinary Study Based on the Co-Production Experience with Rádio UFSCar
Keywords: CTS; Divulgação científica; Interdisciplinaridade; Podcast científico; Rádio UFSCar; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO